The Sedentary Lifestyle of Urban Adolescent Associated with Emotional Eating - Zelyn Damayanti; Ani Margawati; Etika Ratna Noer (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Emotional eating, one of which is eating in the absence of hunger. Eating in the absence of hunger or EAH is a psychological condition that encourages uncontrolled eating. Moreover, EAH is a response to stress factors, external factors, and physical factors in teenagers. In the teenage years, they experience changes both mentally and physically. Besides, teenagers also experience changes in eating behavior. According to previous research, adolescents have a sedentary high lifestyle. A sedentary lifestyle is associated with metabolic limitations that activate hunger signals and will affect a person's hunger and satiety. Therefore, this research aims to determine the relationship between sedentary lifestyle and eating in the absence of hunger in student college. This research used the method of Observational study with a cross-sectional design. Respondents in this study were Diponegoro University students from Kebumen and for research located in Kebumen. The SPSS test used was the Rank-Spearman test for correlation test. Meanwhile, the sedentary lifestyle with eating in the absence of hunger has a significant relationship.